Sayyid Mahmud Taleghani's Economic Thinking Contribution To The Development of The Contemporary Islamic Economy - Achmad Irwan Hamzani; Nur Khasanah (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2023)
This article discusses the contribution of Sayyed Mahmud Teleghani's economic thought to the development of contemporary Islamic economics. To know and understand the contribution of Sayyed Mahmud Teleghani's economic thought to the development of contemporary Islamic economics. The data used are primary data taken from Teleghani's works and secondary data from various documents obtained both online and offline and analyzed descriptively. The results of this article show that as one of the important figures in the Iqtishad school, teleghani transmits many of his economic ideas which play an important role in the development of contemporary Islamic economics. One of the important concepts is about humans as economic actors whereas Teleghani believes that humans have internal principles in the form of a desire for wealth and external impulses that are strongly influenced by the environment and economy. Therefore, three major thoughts become the focus of the economy, namely, property and ownership, freedom, and circulation of money. To achieve harmony, the state must play an important role, especially in decision making and the allocation of resources, the role of the state, prohibiting usury and optimizing zakat, as well as allocating well the concepts of production, distribution, and consumption.